Effects of temperature on N2O production in the process of nitrogen removal by micro-expansion aerobic granular sludge. Issue 59 (19th December 2016) - Chen, Li-Li; Wen, Zhi-Dan; Wang, Wei-Hua; Liang, Hong; Gao, Da-Wen
Abstract: An SBR reactor was used to study the effect of temperature on N2 O production in the process of nitrogen removal by micro-expansion aerobic granular sludge, as well as the removal efficiency of COD and ammonia nitrogen. The experiments were conducted at 21 ± 0.5°C, 26 ± 0.5°C, and 31 ± 0.5°C with low dissolved oxygen. The results showed that simultaneous nitrification and denitrification occurred in this system. The temperature had a significant influence on N2 O production and N2 O release rate; both increased with temperature going up. The ratios of N2 O production to the influent nitrogen loading rate at 31 ± 0.5°C, 26 ± 0.5°C, and 21 ± 0.5°C were 8.07, 5.37, and 3.93%, respectively, which are higher than aerobic granular sludge. N2 O release was 0.96 mg/m 3 at 31 ± 0.5°C, which was 1.43 and 1.37 times the production at 21 ± 0.5°C and 26 ± 0.5°C, respectively, and dissolved N2 O production was 1.46 ± 0.05 mg/m 3 at 31 ± 0.5°C, which was 2.86 and 1.60 times the production at 21 ± 0.5°C and 26 ± 0.5°C, respectively. As a result, 26°C is recommended as a suitable temperature for reducing N2 O emission and maintaining nitrogen removal efficiency in wastewater treatment.